Endodontic and Surgical Management of an Invasive Cervical Resorption in a Maxillary Central Incisor: A Case Report: Invasive cervical resorption - da Cunha Isaltino, Marina; da Silva Souza, Camila; Gomes de Oliveira, Natália; MaurÃcio Reis de Melo Júnior, Paulo; Tavares Velozo Telles, Christianne; Santana de Albuquerque , Diana (Iranian Endodontic Journal, 2023)
The current study aims to report a case of invasive cervical resorption in a maxillary left central incisor with a history of dental trauma. After thorough clinical and tomographic evaluations, cervical cavitation, an irregularity in the gingival contour and crown discoloration were observed. Furthermore, presence of an extensive and well-defined area of invasive cervical resorption with pulp communication was discovered. The suggested diagnosis was asymptomatic irreversible pulpitis. The resorption area was treated with the complete removal of granulation tissue, sealed with light-curing glass ionomer cement. Then, the chemo-mechanical preparation and obturation of the root canal were performed. After two years of clinical follow-up and cone-beam computed tomography examination, there were no clinical signs and symptoms, the filling of the resorption area remained intact, and no hypodense image in the cervical region of tooth #21 could be detected. The management reported in this case presented a possible viable treatment for invasive cervical resorption, provided that correct diagnosis is made.